2022
DOI: 10.1001/jamanetworkopen.2022.2318
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Mass Index in Midlife With Morbidity Burden in Older Adulthood and Longevity

Abstract: This cohort study uses Medicare claims data to investigate the association between body mass index midlife and morbidity burden, longevity, and health care costs in adults 65 years or older.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The paper revealed a close relationship between body mass index indicators and the presence of comorbid conditions, these data are consistent with the data by Khan et al . [ 22 ] obtained during a prospective cohort study of 29,621 patients. Based on the data obtained, it was found that lack of physical activity is one of the main factors contributing to the obesity epidemic, and it is often the goal of intervention, because it is amenable to change at the individual level, which does not contradict the data presented by Wiklund [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper revealed a close relationship between body mass index indicators and the presence of comorbid conditions, these data are consistent with the data by Khan et al . [ 22 ] obtained during a prospective cohort study of 29,621 patients. Based on the data obtained, it was found that lack of physical activity is one of the main factors contributing to the obesity epidemic, and it is often the goal of intervention, because it is amenable to change at the individual level, which does not contradict the data presented by Wiklund [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The total cost of treating obesity and related comorbidities is very high and continues to grow, which is reflected in the indirect impact on the well-being of society and its productivity [21]. According to Khan et al [22] in the US, on average, spending per person in old age is significantly higher among overweight participants (12,390 USD [US Dollars] 95% confidence interval [CI] USD 10,427-14,354) and people with grade I and II obesity (USD 23,396, 95% CI USD 18,474-28,319) compared with participants with normal BMI (p < 0.001). Against the background of the COVID-19 pandemic, obesity was considered a clinically significant risk factor for severe disease [23].…”
Section: Introductionmentioning
confidence: 99%
“…[73][74][75][76][77] In addition to greater burden of CVD, data demonstrate earlier onset of CVD among those with poor CKM health. [78][79][80] Herein, we review the evidence for risk markers of CKM health and their utility to improve precision and accuracy of risk assessment.…”
Section: Novel Risk Markers For Cvd and Ckm Health Metricsmentioning
confidence: 99%
“…Obesity is a major health problem that increases the risk of cardiovascular diseases and shortens life expectancy [ 1 , 2 ]. However, in cardiac and non-cardiac surgery better outcome has been reported in overweight and obese than in normal weight patients, typically with a U-shaped association between body mass index (BMI) and mortality [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%